GURAH AND TRADITIONAL MEDICINE IN HADITH: Challenges and Potential in Modern Era - Munandar, Munandar; Harahap, Alwi Padly (Ulul Albab: Jurnal Studi Islam, 2025)
Gurah, a traditional Islamic medical practice, faces a critical juncture marked by conflicting interpretations of hadith and the dominance of evidence-based biomedicine. This study investigates the epistemological position of gurah within hadith literature, its reception among contemporary scholars and practitioners, and its potential role in modern integrative healthcare. Employing a descriptive-analytical method, the research draws on primary hadith sources referencing medical practices and in-depth interviews with gurah practitioners affiliated with Jam’iyyah Ruqyah Aswaja (JRA) in North Sumatra. Thematic analysis reveals two primary scholarly perspectives: one affirms gurah as part of prophetic medicine, emphasizing its preventive and therapeutic values in line with Islamic health ethics; the other maintains a more critical stance, underscoring the need for empirical validation through modern clinical studies. The study highlights a pressing challenge: gurah must establish scientific credibility without losing its Islamic identity. Nevertheless, it continues to serve communities committed to traditional healing methods. The persistence of gurah in grassroots healthcare illustrates the resilience of Islamic medical traditions amid global medical homogenization. Moreover, its practice reflects a living dialogue between faith-based healing and modern science. The findings propose an interdisciplinary model that integrates gurah into contemporary medical discourse through collaboration between Islamic scholars and biomedical experts. Such a framework not only preserves religious authenticity, but also aligns with global standards of healthcare efficacy and safety. By foregrounding a rarely examined intersection of hadith studies, traditional healing, and medical science, this study contributes to a more inclusive and culturally rooted understanding of healthcare, urging further exploration of Islamic medical heritage within modern scientific paradigms.